Study on the Biological Characteristics of Pegagan Duck - Meisji L. Sari; R.R. Noor; Peni S. Hardjosworo; Chairun Nisa (Research Center for Sub-optimal Lands (PUR-PLSO), Universitas Sriwijaya, 2012)
Sari et al. 2012. Study on the Biological Characteristics of Pegagan Duck. JLSO 1(2):170-176. Pegagan duck is one of the local genetic and biodiversity resources in South Sumatera which needs to be conserved and developed. So far, scientific data of Pegagan duck as a biodiversity resource were relatively limited compared to other local ducks. The aim of this experiment was to investigate and identify egg variability of Pegagan duck. This experiment started by collecting 500 Pegagan’s egg from three districts, namely Tanjung Raja, Inderalaya and Pemulutan, Ogan Ilir Regency, Sumatera Selatan. Collected eggs were cleaned with lysol 2.5% prior to putting into the hatching machine. During hatching process, the eggs were rolled up and down from the 3th d until the 25th d. Egg candling was done three times: day 5, day 13 and day 25. The results showed that initial weight of parent (G0) male and female Pegagan duck was 36.87 g and 36.73 g, respectively. Meanwhile, F1 generation was 36.90 g for male and 37.09 g for female. The growth pattern between male and female duck was relatively the same. Growth curve which showed the relationship between body weight and age of duck formed a sigmoid curve. The growth differences between male and female duck occured at the 5th week. Body weight of male duck was higher than female duck. The highest body weight found at the inflexion point for both male and female duck for parent (G0) was at the 4th week and for F1 was at the 5th week. At the first laying, the body weight of Pegagan duck for parent (G0) reached 1541.17±132.19 g, whereas for F1 reached 1605.34±167.19 g. Parent (G0) and F1 of Pegagan duck layed at the average age of 153 and 154 d, wherein 30% layed at the age of < 151 d and 60% at the age of 151-170 d.These results were expectedly become database and guidance for the conservation and sustainable development of pegagan duck.